2013
DOI: 10.1007/s13181-013-0289-8
|View full text |Cite
|
Sign up to set email alerts
|

Dog and Cat Exposures to Hazardous Substances Reported to the Kansas State Veterinary Diagnostic Laboratory: 2009–2012

Abstract: Pet dogs and cats in the USA are commonly exposed to potentially hazardous substances found in domestic environments. Requests for assistance and advice received by the Kansas State Veterinary Diagnostic Laboratory regarding exposures in dogs and cats to substances perceived by their caretakers to be potentially harmful included 1,616 phone calls, over a 3-year period covering 2009-2012. Enquiries occurred more often during summer. Dogs were involved in 84.7 % of calls and cats in 15.3 %. Oral exposures were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 9 publications
3
10
0
3
Order By: Relevance
“…Drugs intended for human use have accounted for~30% of reported pet poisoning in the USA McLean and Hansen, 2012;Mahdi and Van der Merwe, 2013). Similar proportions have also been reported from Europe (Curti et al, 2009;Caloni et al, 2014).…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…Drugs intended for human use have accounted for~30% of reported pet poisoning in the USA McLean and Hansen, 2012;Mahdi and Van der Merwe, 2013). Similar proportions have also been reported from Europe (Curti et al, 2009;Caloni et al, 2014).…”
Section: Introductionsupporting
confidence: 60%
“…Chemical structure References Acetyl salicylic acid Salycilates Jones et al, 1992;Giuliano Albo and Nebbia, 2004;Cope et al, 2006;Berny et al, 2010;Khan and McLean, 2012;Mahdi and Van der Merwe, 2013;Caloni et al, 2014 Diclofenac Phenylacetic acids Campbell and Chapman, 2000;Khan and McLean, 2012;Caloni et al, 2014 Ibuprofen Proprionic acids Spyridakis et al, 1986;Jones et al, 1992;Poortinga and Hungerford, 1998;Campbell and Chapman, 2000;Giuliano Albo and Nebbia, 2004;Cope et al, 2006;Monaghan and Sutton, 2008;Berny et al, 2010;Khan and McLean, 2012;Mahdi and Van der Merwe, 2013;Bolfer et al, 2014;Caloni et al, 2014 Indomethacin Indole acetic acids Jones et al, 1992;Campbell and Chapman, 2000;Khan and McLean, 2012;Caloni et al, 2014 Meloxicam Oxicams Khan and McLean, 2012;Caloni et al, 2014 Naproxen Proprionic acids Campbell and Chapman, 2000;Cope et al, 2006;Khan and McLean, 2012;Caloni et al, 2014Nimesulide Sulphonamides Borku et al, 2008Caloni et al, 2014 Table 2 Cases of paracetamol (acetaminophen) ingestion reported in dogs and cats. Schlesinger, 1995;Richardson, 2000;Mariani and Fulton, 2001;…”
Section: Nsaidmentioning
confidence: 99%
See 2 more Smart Citations
“…As intoxicações por praguicidas são uma realidade em todo o mundo (GRENDON;BAUM, 1994;COVACI et al, 1999;NELSON et al, 2001;SINGH et al, 2007;GIADINIS et al, 2009;KUMAR et al, 2009;CAMPELO;CALDAS, 2010), o que também inclui os animais (GRENDON;BAUM, 1994;FRAZIER et al, 1999;SPINOSA, 2007c;GIADINIS et al, 2009;DE SIQUEIRA et al, 2012;MAHDI;VAN DER MERWE, 2013). Os praguicidas carbamatos aldicarbe e carbofurano, que são potentes inibidores da enzima acetilcolinesterase e altamente tóxicos (BARON;MERRIAM, 1988;BARON, 1994;GUPTA, 1994;PROENÇA et al, 2004;ASCHNER, 2006), são comumente utilizados para intoxicar intencionalmente pessoas (NISSE et al, 2002;PROENÇA et al, 2004;REBELO et al, 2011;ZHOU et al, 2011; SAKUNTHALA TENNAKOON; KARUNARATHNA; UDUGAMPALA, 2013) e animais (FRAZIER et al, 1999;MOTAS-GUZMÁN et al, 2003;SPINOSA, 2007c;OTIENO et al, 2010;ANASTASIO;SHARP, 2011;ARNOT et al, 2011;NOVOTNÝ et al, 2011;DE SIQUEIRA et al, 2012).…”
Section: Discussionunclassified